Are Effects of COVID-19 Understated? Gender-Based Implications on Income, Coping Strategies and Time Allocation in Ethiopia - Kebede, Sindu W.; Maruta, Admasu A; Geda, Nigatu R (Advances in Social Sciences Research Journal, 2024)
This study investigates impacts of COVID-19 on household income, coping strategies, and time allocation challenges using gender-differentiated approach. Data from two rounds of phone surveys conducted in Ethiopia were used. The findings reveal significant impacts of COVID-19 and its containment measures on the income of both male-headed (50 percent) and female-headed households (44 percent). In response to income decline, majority of male (70 percent) and female (64 percent) respondents resorted to saving as a coping strategy. This outcome underscores the prevalent gender disparity in financial inclusion within Ethiopia. A comparative analysis of time allocation for reproductive and domestic activities before and during the pandemic indicates that women allocated more hours than men to these tasks. It is, therefore, crucial to acknowledge and assign value to women's contributions, given their predominant role in reproductive and domestic activities. These activities are essential components of daily life within households and contribute significantly to the overall economy.